Kocuria dacryocystitis infection, caused by kocuria ocularis sp. Nov. Issue 2 (June 2014) - Domont, Fanny; Le Flèche‐Matéos, Anne; Brémond‐Gignac, Dominique; Hamdad, Farida
Abstract : Introduction: Kocuria spp. rarely cause infectious disease but can be opportunistic pathogens in immunocompromised patients. The numbers of documented infections are low but rising. Case presentation: A 74‐year‐old woman presented with acute, painful swelling of the medial canthus of the left eye. The skin surface was red and acutely painful to the touch. Because of several clinical relapses despite antibiotic treatment, surgical dacryocystorhinostomy with marsupialization of the lacrimal sac into the nasal cavity was performed. Lacrimal sac drainage samples were analysed and yielded Kocuria . This is, to our knowledge, the first case of Kocuria dacryocystitis. Furthermore, the dacryocystitis was caused by a novel species of Kocuria, which we suggest should be named Kocuria ocularis . Conclusion: Kocuria related to ocular infection has not yet been documented. This report expands the clinical spectrum of diseases caused by these potentially underestimated pathogens.